Electromagnetic modeling of 35kV distribution transformer lightning overvoltage and its prevention method. Issue 1 (July 2021) - Liu, Zhenguo; Zhao, Puzhi; Yang, Zhushi; Wang, Jie; Zhou, Qipei; Cheng, Tingli; Chen, Zhiwei; Zhang, Yingying
Abstract: Distribution transformers are important power conversion equipment, whose safe and reliable operations affect the power supply quality of the distribution network. In order to analyze the lightning strike fault of distribution transformers, some more reasonable protection measures of transformers could be put forward. In this paper, a 35kV distribution transformer under the lightning strike is taken as the research object. Firstly, the lightning overvoltage model of the distribution transformer was established with the method of the double exponential model. Secondly, through the simulation of the distribution transformer, it was found that the electromagnetic transient distribution change dramatically, which will quickly cause the winding current flickering and form the winding overvoltage. Finally, through the voltage distribution law and the magnetic flux distortion of the transformer, it can be seen that the lightning overvoltage has a serious effect on the electromagnetic parameters of the transformer. The protection scheme is briefly analyzed, which has a guiding significance for the lightning protection design of distribution transformers.